18F-FDG-PET/CT for Evaluation of treatment response in high grade lymphoma - Kumar, Yadav Ajay; Rakesh, Kumar; Arun, Malhotra; Atul, Sharma (Nepalese Journal of Cancer, 2017)
18F-FDG PET is highly sensitive and specific for evaluation of the treatment response of high-grade lymphomas. The molecular information provided by 18F-FDG-PET identifies the functional content of anatomic finding and helps to categorize their nature as malignant or benign. On the other hand, the CT data obtained in the same setting provides anatomical localization of the 18F-FDG-PET data while also improving the FDG-PET image quality as it is utilized for attenuation correction. Previously, most of the studies were done on this topic by using 18F-FDG-PET alone. Present study was planning to assess the role of 18F-FDG-PET/CT in evaluation of treatment response in patient of HD and NHL. Results showed that 43 patients out of 52 showed no pathologic FDG uptakes, whereas 9 showed persistent uptakes. Among the 43 patients who had negative PET scans, only three relapsed, whereas among the 9 patients who had persistent abnormal 18F-FDG uptakes on post therapy PET/CT scans, two recovered. The sensitivity, specificity, positive and negative predictive values and accuracy of post therapy PET/CT scan was 70%, 95%, 78%, 93%, and 90% respectively.